Diferenciação camponesa na depressão sertaneja semi-árida do Ceará - Vidal, Déa de Lima (2009)
The impacts provoked by determined technological st andard components of the adopted by Brazilian agriculture had been analyzed on the s ocial production relations in agricultural Familiar Units (FUs) of the Sertaneja Depression, S emi-arid area of Ceará, Brazil. 96 FUs had been differentiated from original data in regar ds to the factor work composition and productivity and mechanization level. The follow ou tstanding results were found: (i) the sazonal wage-earning work presence in all the agric ultural FUs, excepting in the Tapera Community and (ii) the majority of the FUs had pres ented mechanization low index. Thus, the Tapera, Queimadas and Lustal II FUs had constit uted those Communities had suffered the minors familiar work internal transformations, related to the low mechanization, characterizing theirselves thus, as peasants. These FUs can serve of base for structuring an alternative model of development, in the opposit e to the globalizer rationality. The high intensification of its factor work, indicating its maximum mobilization allied to low mechanization dependence and the important young ru ral people presence, allows to glimpse that still those rural communities UFs cont rol resources of this agrarian disadvantaged and threatened system, inviting for i ts restoration and perfectioning.